Textual Analysis of the Short Stories of Francis J. Kong - Elmira Rodriguez; Chorla Napigkit (Philippine Association of Institutions for Research, Inc., 2020)
The short story as a literary genre mirrors life, which touches the emotions of the readers. This study employs qualitative analysis using the inspirational stories of Francis J. Kong, namely Scarred Hands, Sweet Success, and The Most Important Ingredient in Service, False Conclusions, and Sweet Revenge. The characters' responses to various incidents were analyzed and compiled from consolidated opinions and feelings to assure that contextual presentation is considerable. Internal conflicts of Francis J. Kong's stories are choices between optimism and pessimism, determination and resignation, egoism and altruism, being impulsive and restrained, as well as tranquility and turmoil. Meanwhile, external conflicts are options between trust and wealth, positivity and negativity, declination and approval, indifference and concern, ill-mannered and gracious. These conflicts, resolutions, and morale are believed to boost readers' strength, confidence, and collaboration with others. The main characters' choices demonstrate the values of creative thinking, acting, sharing constructive outlook, and rekindling the hearts that relates to the readers' experiences and perspectives. Resolutions narrated are directed towards acceptance of failure and defeat conceptualized through self-realization from a conventional perspective. The moral lessons commonly constitute the virtue of acclimatizing the essence of goodness and reverence of life, as the outgrowth of building one's strength, values, and faith in God that would translate an epitome of humanity